SAS Institute - Bankert, Ellen; Lee, Mary Dean; Lange, Candice (Senate Hall Academic Publishing, 2005)
This case explores how and why SAS Institute has been so successful in a turbulent industry and a challenging, highly competitive business environment and what role its leader has played in that success. SAS Institute is a privately held software company based in North Carolina that experienced double digit revenue growth from 1976 when it was founded by the current CEO, Jim Goodnight, to 2000 when this case was written. What is most unique about this company, however, is a work environment and culture designed to promote contented and motivated employees by providing interesting, satisfying work in a physical setting that offers very generous perks for employees and their families, like on-site medical care, a full gym and fitness center, and childcare center plus a 35 hour work week. As a result of the CEO’s vision of the kind of workplace he wanted his company to be, long before the term family-friendly was even coined, SAS has consistently broken industry records on annual employee turnover rates and has won recognition in numerous surveys on “Best Places to Work” surveys in such magazines as Fortune, Business Week.
Keywords: leadership; work environment; work and family; organizational culture; employee-centered; organizational strategy; family-friendly